COMPARATIVE EVALUATION OF HEPATOPROTECTIVE EFFECTS OF KATACIN AND GERANIL ON A MODEL OF ACUTE TOXIC LIVER DAMAGE - Khushbaktova, Z.A.; Inoyatova, F.Kh.; Kurbanova, N.N.; Aslanova, A.Kh. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
to evaluate the effectiveness of new domestic drugs (cavergal, geranyl and catacin) in the correction of the main hepatic syndromes: cytolysis, cholestasis, mesenchymal inflammation and hepatocellular insufficiency in a model of toxic liver damage. Material and methods: studies were conducted on 75 male rats with acute toxic liver damage, which was reproduced by administering heliotrin at a dose of 200 mg / kg, 8 rats were included into intact group. Biochemical studies of blood serum were performed on a biochemical analyzer. Results: experimental pharmacotherapy of acute toxic liver damage with new drugs katatsin and geranil significantly reduced rates of cytolysis, cholestasis, mesenchymal inflammation. The preparations increased the protein synthesis function of the liver. According to hepatoprotective properties, catacin and geranil were not inferior to Karsil to the hepatoprotector and significantly outperformed the antihypoxant of the cavergal. Conclusion: the plant flavonoids catacin and geranyl have pronounced hepatoprotective properties.